MEMBANGUN KERJA SAMA NEGARA-NEGARA ASEAN DALAM MENGANTISIPASI PERLUASAN JARINGAN TERORISME DI INDONESIA - Arifiyanto, Muhammad Naufal (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2015)
ASEAN formed pursuant to Declaration of Bangkok on 8 August 1967 signed by five figure founder of ASEAN. ASEAN represent intergovernmental international organization with membership of regional for the purpose of and target of international organizational public which have pattern and distinguish area which its activity area very wide and public and also ASEAN have shown its ability as one of international organization which have fulfilled conditions a international organization. ASEAN of Nations the including Indonesia as member of ASEAN have been given on to heavy challenge namely era fight against terrorism. This proven at decade in year 2009 and till now in the year 2011 as does arrest of Dusty Ustad Abu Bakar Ba'Asyir in Central Java, and till now in course of justice is ecsess than era fight against terrorism. ASEAN of nations have taken legal efforts in anticipating extension of terrorism network in Indonesia through international is same activity. Problems which can be lifted on the surface of, where to this moment terrorism problematica still become serious threat to society, governmental and state in the world in general, and also in Indonesia especially namely same activity what have been taken by ASEAN of nations in anticipating extension of terrorism network in Indonesia and how implication of yuridis-sosiologis of execution of same activity between ASEAN of nations in anticipating extension of terrorism network in Indonesia.